Assessment of the right ventricle by magnetic resonance imaging in chronic obstructive lung disease. Issue 8 (August 1990) - Turnbull, L W; Ridgway, J P; Biernacki, W; McRitchie, H; Muir, A L; Best, J J; MacNee, W
Abstract : Right ventricular wall and chamber volume were measured by magnetic resonance imaging in 16 patients with stable chronic obstructive lung disease who subsequently underwent measurement of pulmonary haemodynamics by right heart catheterisation. The patients had a forced expiratory volume in one second of 0.7 (SD 0.3) litres, a forced vital capacity of 2.4 (1.0) l, an arterial oxygen tension (PaO2) of 6.5 (1.3) kPa, an arterial carbon dioxide tension (PaCO2) of 6.5 (1.0) kPa, and a mean pulmonary arterial pressure 30 (10) mm Hg. The mean right ventricular free wall volume was 57.1 (22.6) cm3, compared with a mean value of 115.0 (44.3) cm3 for the left ventricle and interventricular septal volume. The right ventricular chamber volume at end systole was 44.8 (23.4) cm3, whereas the left ventricular end systolic chamber volume was 51.1 (35.1) cm3. The right ventricular free wall volume correlated with the right ventricular chamber volume (r = 0.71), systolic (r = 0.74) and mean (r = 0.72) pulmonary arterial pressure, pulmonary vascular resistance (r = 0.67), and PaCO2 (r = 0.56). There was no significant correlation between the right ventricular free wall volume and PaO2 or the right ventricular ejection fraction, measured by radionuclide ventriculography. Assessment of the right ventricle by magnetic resonance imaging may help to better define patients with cor pulmonable and assess the long term effects of treatment in such patients.